The Medicolegal Application of Artificial Intelligence as Doctors’ Medical Assistants in Medical Services in Indonesia - Sugihardana, Danang; Rizka; Azhari, Aidul Fitriciada (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study examines the implementation of AI in medical services in Indonesia from a medicolegal perspective, highlighting the urgent need for the development of a robust legal and ethical framework to ensure responsible and safe use of AI while protecting patients' rights and privacy. The problem of the research is to analyze how medical ethics and the positive law in Indonesia regulate the application of Artificial Intelligence (AI) as medical assistance for doctors in medical services. This research employed a combination of the normative juridical approach method and the conceptual analysis approach. Results found that AI regulations in Indonesia are still in the developmental stages and lack specificity. Thus, in cases of errors in AI usage, the legal responsibility remains with the doctors who employed this technology as a tool. This underscores the importance of stringent oversight and the development of more detailed regulations as AI adoption in the medical sector in Indonesia continues to grow.